Mechanical Properties of Polyester Matrix Composites with Carbon Hybrid Reinforcement and Woven Wire - Gerald Adityo Pohan (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2021)
This study is aimed to determine the mechanical properties of composite materials using hybrid reinforcing materials, namely carbon fiber and woven wire. The variations in the composition of the matrix / carbon fiber / woven wire (in%) used were 70/0/30, 70/30/0, 70,20 / 10, 50/30/20. The mechanical tests performed were the tensile test (ASTM D 638-03) and the impact test (ASTM D 6110). The results show that the composites with the composition 50/30/20 have the highest tensile and impact strength. Specimens with the highest carbon fiber content have better tensile strength.